New and poorly known species of the genus Brachyllus Brenske, 1896 (Coleoptera: Scarabaeidae: Melolonthinae) from China - Zhao, Ming-Zhi; Qi, Zhi-Hao; Su, Rong-Xiang; Liao, Tao-Kun (Zootaxa, 2023)
Three new species of the genus Brachyllus Brenske, 1896 are described from China including Brachyllus songhaitiani Zhao, Qi, Su & Liao, new species from Fujian and Jiangxi, B. dongzhiweii Zhao, new species from Xizang and B. tangzhaoyangi Zhao, new species from Guangxi. Brachyllus langeri Keith, 2008 is downgraded to a subspecies of B. rougeriei Keith, 2003 and reported from China for the first time. Newly collected material of B. deuveianus Keith, 2003 allows better definition of its variability. A distribution map for this genus is also presented.